Mitofusin 2 Is Essential for IP3-Mediated SR/Mitochondria Metabolic Feedback in Ventricular Myocytes - Seidlmayer, Lea K.; Mages, Christine; Berbner, Annette; Eder-Negrin, Petra; Arias-Loza, Paula Anahi; Kaspar, Mathias; Song, Moshi; Dorn, Gerald W.; Kohlhaas, Michael; Frantz, Stefan; Maack, Christoph; Gerull, Brenda; et al. (Frontiers in Physiology, 2019)
Endothelin-1 (ET-1) and Angiotensin II (Ang II) are multifunctional peptide hormones which regulate the function of the cardiovascular and renal systems. Both hormones increase the intracellular production of inositol-1,4,5-trisphosphate (IP3) by activating their membrane-bound receptors. We have previously demonstrated that IP3-mediated sarcoplasmic reticulum (SR) Ca2+ release results in mitochondrial Ca2+ uptake and activation of ATP production. In this study, we tested the hypothesis that intact SR/mitochondria microdomains are required for metabolic IP3-mediated SR/mitochondrial feedback. As a model for disrupted mitochondrial/SR microdomains, cardiospecific tamoxifen-inducible mitofusin 2 (Mfn-2) knock out (KO) mice were used. Mfn-2 tethers SR to mitochondria in healthy cells. When the physical link between SR and mitochondria by Mfn-2 was disrupted, the SR/mitochondrial metabolic feedback mechanism was severely impaired resulting in inability of the IP3-mediated SR Ca2+ release to induce ATP production in Mfn-2 KO mice. Our study demonstrates that in cardiomyocytes ET-1 signaling is required for maintaining normal cardiac function and bioenergetics. We further show that when the physical linkage between SR and mitochondria by Mfn-2 was disrupted, the SR/mitochondrial metabolic feedback mechanism was severely impaired resulting in inability of the IP3-mediated SR Ca2+ release to induce ATP production. This finding further supports the importance of intact SR/mitochondria microdomains in cardiac myocytes.